2020
DOI: 10.1186/s12986-020-00474-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metabolically healthy obesity on the development of arterial stiffness: a prospective cohort study

Abstract: Background: Metabolically healthy obesity (MHO) has been reported to be associated with the development of vascular damage by the carotid intima-media thickness, but the relationship between metabolic health and obesity phenotypes and arterial stiffness is still unknown. Our hypothesized that different metabolic health and obesity phenotypes might be associated with the development of arterial stiffness, and that subjects in MHO phenotype might not have increased risks of arterial stiffness compared with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 45 publications
2
14
1
Order By: Relevance
“…The MESA study [ 35 ] found that the inverse relationship between arterial stiffness and BMI remained in the elderly cohort, suggesting that arteries in elderly individuals with normal weight may be less stiff than they appear by measuring BAPWV. Another study found that regardless of the BMI, females are generally more affected by progression of arterial stiffness [ 47 ], while this is not apparent in males. The latter may lend support to other studies which have found BMI to be a crude measures of total adiposity which may inadequately represent body fat distribution and/or body shape [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MESA study [ 35 ] found that the inverse relationship between arterial stiffness and BMI remained in the elderly cohort, suggesting that arteries in elderly individuals with normal weight may be less stiff than they appear by measuring BAPWV. Another study found that regardless of the BMI, females are generally more affected by progression of arterial stiffness [ 47 ], while this is not apparent in males. The latter may lend support to other studies which have found BMI to be a crude measures of total adiposity which may inadequately represent body fat distribution and/or body shape [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another prospective study by Fingeret et al [ 28 ] did not find any difference between MHO and MUO in hypertension incidence after 10.9 years of follow-up (odds ratio (OR): 1.3, CI 95%: 0.8–2.09). Yuan et al [ 29 ] showed that MHO has no association with the development of arterial stiffness (OR: 0.99; CI 95%: 0.61–1.6), while MUO and MUNO phenotypes lead to significantly progressed arterial stiffness (OR: 4.56; CI 95%: 2.60–8) and (OR: 5.05; CI 95%: 3.12–8.19), respectively. On the other hand, some studies by Hashimoto et al [ 30 ] and Gilardini et al [ 31 ] did not see any association between MHO and the risk of renal failure, prediabetes, diabetes and CVDs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that obese individuals had youthful arteries with lower PWV [24,25]. Moreover, a prospective cohort study found an irrelevant association between them [26]. Obesity often coexists with other risk factors and accelerates arterial stiffness through its associated metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 99%